Comparison of Narcotic Criminalization Rules in Malaysia and Indonesia - Dwi Priyatmojo, Katon (Activa Yuris: Jurnal Hukum, 2023)
This study aims to determine the comparison of narcotics criminalization rules between Malaysia and Indonesia. The method used in this research is normative legal research. This method is carried out by collecting secondary data through literature studies by reading laws, library books, and documents related to this research topic. Data obtained from library data processing were analyzed qualitatively. In Malaysia, drugs are the single most complicated social problem. Since 1970 until now there is still no visible positive change, in fact it has become more flexible and has not been able to be stopped. Malaysia has made various efforts to eradicate narcotics offenders in their country, including by conducting various studies on the dangerous contents of these narcotics by involving universities and institutions, establishing a special agency for eradicating narcotics crimes, spending large amounts of money in efforts to rehabilitate drug convicts. Meanwhile, in Indonesia the pattern is still applied to eradicating narcotics abuse, victims of drug users are still put in jail, even though during the process prisoners are allowed to be rehabilitated, this has not been an effective solution. Even though the Indonesian government's efforts to decriminalize or change the paradigm from imprisonment to recovery already exist in Supreme Court Circular (SEMA) Number 4 of 2010 concerning Placement of Abuse, Victims of Abuse and Narcotics Addicts in Institutions for Medical Rehabilitation and Social Rehabilitation and Government Regulation Number 25 of 2011 concerning Compulsory Implementation Reports for Narcotics Addicts whose content confirms that drug addicts are victims and not perpetrators of crime, as well as legal legitimacy that addicts are not perpetrators of crimes but someone who suffers from addiction requires treatment both physically and psychologically and requires support from the community to be able to return to normal life, but in its implementation it is very difficult to implement so that it is still dominantly using criminalization efforts or still using the imprisonment paradigm instead of the recovery process for drug convicts